Hank the Cowdog: The Disappearance of Drover - Book 57 - Erickson, John R. 1943-; Holmes, Gerald L. (Perryton, TX : Maverick Books, 2012)
Hank and Drover are excited when a quick nap in the back of Slim's pickup turns into a trip to town. But the excitement turns to drama when they find themselves at the livestock show--and Drover decides to take off to visit his mother. Can Hank track down his faithful sidekick before Slim heads back to the ranch? Or is he off on a wildgoose chase?
Keywords: Hank the Cowdog (Fictitious character) -- Juvenile fiction; Dogs -- Juvenile fiction; Missing persons -- Juvenile fiction; Ranch life -- Juvenile fiction -- Texas; Hank the Cowdog (Fictitious character) -- Fiction; Dogs -- Fiction; Lost and found possessions -- Fiction; Ranch life -- Fiction -- Texas; Texas -- Juvenile fiction; Texas -- Fiction